Perbandingan Metode SAW, WP, dan TOPSIS Dalam Pemilihan Bibit Cabai Rawit - Rizki Maulana; Dede Imana Yulianto; Febrian Irfan Syafiq; Muhammad Syaugi; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The concept of a decision-making aid program is currently growing rapidly. Currently there are many methods that can be used to assist decision making. There are 3 methods that can be used to help solve problems in multi-attribute decision making; SAW, WP and TOPSIS methods. because the method is easy to understand, simple, efficient in terms of computation and has the ability to measure the relative value of an alternative decision using simple mathematical calculations. The purpose of this research is to help and facilitate every farmer in the process of selecting cayenne pepper seeds. In this study, the results were obtained in the form of cayenne pepper seeds which had yields and growth processes that were in accordance with what was expected by farmers, namely tick cayenne pepper seeds.